The Frequency Of Maternal Near Misses At Benazir Bhutto Hospital- Using The WHO Standard Tool, A Cross-Sectional Study - Humaira Masood; Tallat Farkhanda; Sadia Khan; Ismat Batool; Nighat Naheed; Hina Gul (Journal of Rawalpindi Medical College)
Objective: To analyse maternal near-miss frequency and causes on WHO-based tools at a government hospital.